SUNFLOWER WAX-BASED OLEOGEL FROM OILS REFINING WASTES AS A SHORTENING ALTERNATIVE IN CUPCAKE - Abd El-hamied, Asmaa; Mohamed, Hanaa; Abdelgawad, Ahmed (Food and Feed Research, 2026)
This investigation utilized sunflower wax, a by-product recovered from sunflower oil refining waste, to prepare a sunflower oil-based oleogel (SFW-BO) and evaluated its potential as a full replacement for conventional palm oil-based shortening (SH-BPO) in bakery applications. The novelty of this study lies in the use of sunflower wax obtained directly from oil refining waste, rather than commercial wax, emphasizing resource sustainability. Fourier-transform infrared (FTIR) spectroscopy confirmed the effectiveness of the purification process in producing high-purity wax. Physicochemical characterization demonstrated that 100% SFW-BO exhibited superior oil-binding capacity (OBC ≈ 99%) and a higher melting point (53.2°C) compared to SH-BPO (40.1°C). Fatty acid profiling revealed that increasing the proportion of SFW-BO significantly reduced saturated fatty acid content from 50.61% (100% SH-BPO) to 11.15% (100% SFW-BO), while increasing unsaturated fats. Cupcakes formulated with SFW-BO blends showed enhanced specific volume and reduced textural hardness, with the 100% replacement sample achieving the highest volume (1.86 cm³/g). Water activity and sensory analyses indicated no significant differences between shortening and oleogel-containing cupcakes, suggesting comparable microbial stability and consumer acceptability. These findings establish refining waste-derived sunflower wax oleogel as a functionally robust and nutritionally advantageous alternative to traditional shortening, enabling the production of baked goods with a reduced saturated fat footprint without compromising technological performance or sensory quality.